Effect of honeybees pollination on seed setting, yield and quality characteristics of rapeseed (Brassica napus oleifera) - Oz, M; Karasu, A; Cakmak, I; Goksoy, A T; Ozmen, N (The Indian Journal of Agricultural Sciences, 2008)
The study was conducted during 2004-06 to determine the effects of pollination using honeybees on seed yield and quality characteristics of the rapeseed 'Pulsar' winter variety of canola (Brassica napus ssp. oleifera) was grown and small colonies of honeybee (Apis mellifera anatoliaca) were placed in mini hives with or without pollen trap. The present study contained 4 pollination treatments, viz. T1, an open field; T2, a cage without bees, T3, a cage with bees in a regular mini hive and T4 a cage with bees mini hive with pollen trap. Seed yield was 3 205, 1 823, 2 360 and 2 357 kg/ha for the treatments T1, T2. T3 and T4 respectively. The differences in pods/plant, seeds/pod and seed yield/plant were found significant (p&lt0.05) and highest values were obtained from open field, followed by a cage with bees in a regular mini hives and a cage with bees in a bottom pollen trap hive. Seed weight, branches/plant, harvest index, seed protein and oil content were insignificantly influenced by treatments. Honeybee pollination increased the seed yield significantly but not protein and oil percentage in seeds.